GEOGRAPHICAL CARTOGRAPHY: WHAT CAN A MAP ... - Roos, Djeovani; Ferraz, Claudio Benito O. [UNESP] (Univ Federal Fluminense, 2017)
Think the map is think of it as the freight forwarding, forces of lines/bodies affect and point to senses of place and spatial orientation. Unfolds that the maps are not restricted to flat representation of the Earth's surface, so there are other ways to relate and experience the representations that the mapping process promotes. The spatiality is constituted in the multiplicity and the relationship of cartography should be included in the suppleness and the spatial map of the world happen himself. What makes a map is one of the prerogatives eloquent that fall on the mapping process. Thus, we capture and show spatial information are modes of apprehension of a possible of what makes an image be a cartographic map. Emphasises that the directions of this work are in order to think about the possibilities and potentialities for the Cartographic processes and creating maps. Seeking to shift cartographic thought, rubbing their communicative and informational dimensions to which she links these days. The power which introduces here is instigating the thought in relationship of maps with artistic production; While artwork is not fixed but representatively is an instigator of possible processes. The mural Polimorfia Fronteirica, exposed on FCH/UFGD, comes here as a possible in conjunction with the geographic and cartographic thought, in which the maps are glimpsing at contingencialidade creative thinking/living the world while place.
Keywords: Map; Geographical Cartography; Multiplicities; Geographic Thought